EFEKTIVITAS INTERVENSI POSITIF BERBASIS 5S (SENYUM, SALAM, SAPA, SOPAN, DAN SANTUN) UNTUK PENGUATAN KARAKTER KEPEDULIAN SISWA MTSN 3 TUBAN - Kartika Hidayati; Anis Sa’adah (PT. Hasba Edukasi Mandiri, 2025)
In the era of globalization, character education is a crucial issue in developing a young generation with ethical and social awareness. The caring character of students in Indonesia, particularly in Islamic schools (madrasah), shows a decline in moral and social values due to the influence of digital technology and a lack of positive interactions. This phenomenon threatens social stability and the readiness of the younger generation to become responsible and empathetic citizens. This study examines the effectiveness of a positive intervention based on the 5S culture (Smile, Greet, Greet, Polite, and Courteous) in strengthening the caring character of students at MTsN 3 Tuban through a qualitative, explanatory descriptive method, collecting data from interviews, observations, and documentation. The results indicate that this intervention significantly increased students' empathy, respect, and social awareness, despite challenges during the initial adaptation phase. Limitations of the study include its coverage in a single location and limited subjects. It is recommended that the implementation of the 5S culture be carried out sustainably, involving the entire school community, to optimize its positive impact and expand its application to other schools.